Respuesta :

Answer:

36

Step-by-step explanation:

for the equation, we have to add 1 cubed, 2 cubed and 3 cubed together to get the answer. That equation would look like this

1^3 + 2^3 + 3^3

or expanded out

(1x1x1)+(2x2x2)+(3x3x3)

Solving that down, the equation turns into this

1 + 8 + 27

Adding those values together leaves us with 36!

Hope this helped, have a good rest of your day!

Answer:

36

Step-by-step explanation:

[tex]1^{3}[/tex] + [tex]2^{3}[/tex] +[tex]3^{3}[/tex] = 36

[tex]1^{3}[/tex] = 1 x 1 (= 1) x 1 = 1

[tex]2^{3}[/tex] = 2 x 2 (= 4) x 2 = 8

[tex]3^{3}[/tex] = 3 x 3 (= 9) x 3 = 27

27 + 8 + 1 = 36

Hope this helps :)

ACCESS MORE